2008
DOI: 10.1016/j.ejcts.2008.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary endarterectomy: an alternative to circulatory arrest and deep hypothermia: mid-term results

Abstract: The results confirm that adequate removal of pulmonary artery obstructive lesions can also be achieved with an operative procedure that avoids or reduces the use of DHCA while allowing a bloodless field during PEA interventions. This technique may limit the well known adverse effects of DHCA due to organ hypoperfusion, improving the postoperative recovery of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Four prospective studies were identified, 30,38,40,46) ; other studies were either clearly retrospective 6,15,22,25,29,35,42,44,47,48) or not specified. 21,26,33,43) Two studies presented results in a series of CTEPH patients treated surgically and medically 40,47) ; others included only series of surgically treated patients. There was one retrospective study from Austria that compared hemodynamic indices between PTE and non-PTE patients with a 1-year follow-up, but could not be included in the current review due to insufficient data to meet the inclusion criteria.…”
Section: Quality Of Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…Four prospective studies were identified, 30,38,40,46) ; other studies were either clearly retrospective 6,15,22,25,29,35,42,44,47,48) or not specified. 21,26,33,43) Two studies presented results in a series of CTEPH patients treated surgically and medically 40,47) ; others included only series of surgically treated patients. There was one retrospective study from Austria that compared hemodynamic indices between PTE and non-PTE patients with a 1-year follow-up, but could not be included in the current review due to insufficient data to meet the inclusion criteria.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…6) Seven series had more than 100 patients, 6,15,25,38,40,44,47) five had between 50 and 100 patients (range 50-88), 22,29,30,35,43) and the other seven series had less than 50 patients each (range 23-41). 21,26,33,36,42,46,48) The surgical technique was clearly described in one study, 6) and some modifications to Jamieson's technique were described in two studies. 21,36) T h i r t y-d ay m o r t a l it y wa s r e p o r t e d by a l l studies.…”
Section: Quality Of Evidencementioning
confidence: 99%
See 3 more Smart Citations